(untitled) (Derna Academy Journal for Applied Sciences, 2026)
Helicobacter pylori (H. pylori) infection is one of the most common chronic bacterial infections globally, closely linked to multiple gastrointestinal diseases, suffering from gastritis, peptic ulcer disease, and gastric cancer. Epidemiological data about H. pylori infection in Libya are rare, even more so among asymptomatic populations. Note: This cross-sectional study examines the seroprevalence of H. pylori antibodies among university students in Libya and their potential associations with gastrointestinal symptoms and selected medical history variables. The study involved 178 asymptomatic students from five faculties at Misurata University. Demographic and clinical information were obtained using a structured questionnaire, and blood samples were collected via a finger prick. Serological detection of anti-H. There was a test for anti-HP. In all, 10 participants were positive for H. pylori antibodies, with an overall seroprevalence of 5.6%. There was no statistically significant gender difference in seropositivity amongst females (5.5%), and males (6.3%) were found to be comparable. Also, no association was found between infection status and gastrointestinal symptoms or medical history variables, including anaemia, vitamin B12 deficiency, allergy, previous surgery to the gastrointestinal tract, and psychological stress. These findings show that asymptomatic university students had a lower sero-prevalence of H. pylori infection and also suggest the need for larger epidemiological studies to get more information about the extent of this infection in Libya.